Correlation of N2O and ozone in the Southern Polar vortex during the airborne Antarctic ozone experiment - Loewenstein, M.; Strahan, S. E.; Starr, Walter L.; Kelly, K. K.; Proffitt, M. H.; Podolske, J. R.; Chan, K. Roland (1988)
In situ N20 mixing ratios, measured by an airborne laser spectrometer (ATLAS), have been used along with in situ ozone measurements to determine the correlation of N2O and ozone in the Antarctic stratosphere during the late austral winter. During the 1987 Airborne Antarctic Ozone Experiment (AAOE), N2O data were collected by a laser absorption spectrometer on board the ER-2 on five ferry flights between Ames Research Center (37 deg N) and Punta Arenas, Chile (53 deg S), and on twelve flights over Antarctica (53 S to 72 S). Of all the trace gas species measured by instruments on board the ER-2, only one showed a relationship to the N2O/O3 correlations in the vortex. With few exceptions, positive N20/O3 correlations coincided with total water mixing ratios of greater than 2.9 ppmv, and total water mixing ratios of less than 2.9 ppmv corresponded to negative correlations. The lower water mixing ratios, or dehydrated regions, are colocated with the negative correlations within the vortex, while the wetter regions always occur near the vortex edge.